Pelatihan Penggunaan Artificial Intelligence dalam Perencanaan Pembelajaran di Era Revolusi Industri 4.0 Bagi Guru-guru SMA - Purwati, Heni; Nur Aini, Aurora; Wulandari, Dewi; Ramadhani, Ravi Akmar; Lestari, Revita Dwi; Sulaiman, Dini Sailin Nihla Putri (Universitas Muhammadiyah Malang, 2024)
Purpose – The purpose of this PKM (Community Service) activity is to increase literacy in the implementation of AI (Artificial Intelligence) in assisting in preparing learning plans for teachers in SMA Negeri 15 Semarang Design/methodology/approach – The STAR method is used in this PKM activity. At stage S (Situation), teacher needs are analyzed through discussion methods with the head of the curriculum. In stage T (Task), a mapping of activities is carried out that needs to be carried out to answer the needs that have been analyzed previously. The next step, namely A (Action), is the implementation stage. The final phase is R (Result) where the team provides feedback on the participants' work/products at this stage. The object of this activity are the teachers of SMA N 15 Semarang Findings – The PKM activities ran smoothly and even the enthusiasm of the teachers/participants was visible. This was detected from the results of the activity evaluation questionnaire analysis where all (positive) questionnaire indicators were filled with scores of 4 (agree) and 5 (strongly agree). Originality/value –Some impacts felt by teachers are: 1) Before the training, teachers had never applied AI to help in compiling learning devices; 2) Teachers were able to apply AI to help compile learning plans; and 3) Teachers produced work in the form of learning plans by utilizing AI.